How does Performance Employee Enhanced Mindful Leadership of School Employees? - Agastya, Kadek Deva; Meyliana, Henny; Mudjiarto, Hari; Taridi, Taridi; Karsinah, Karsinah (Journal of Economic, Religious, and Entrepreneurship (JoERE), 2023)
This study investigates the effect of mindful leadership and organizational commitment on employee performance in an organizational context. Mindful leadership is a leadership approach that integrates full awareness and attention in managing teams and organizations, while organizational commitment reflects the level of attachment, loyalty, and employee involvement. This study uses a quantitative approach by applying a questionnaire to employees of SMA in Bandar Lampung City. The collected data were analyzed using statistical regression techniques to examine the relationship between mindful leadership, organizational commitment, and employee performance. The results of this study are expected to provide a better understanding of how these factors interact and influence employee performance in the work environment.